2014
DOI: 10.1016/j.jchf.2014.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Capacity and Mortality in Patients With Ischemic Left Ventricular Dysfunction Randomized to Coronary Artery Bypass Graft Surgery or Medical Therapy

Abstract: Objective To assess the prognostic significance of exercise capacity in patients with ischemic left ventricular (LV) dysfunction eligible for coronary artery bypass surgery (CABG). Background Poor exercise capacity is associated with mortality, but it is not known how this influences the benefits and risks of CABG compared to medical therapy. Methods In an exploratory analysis physical activity was assessed by questionnaire and 6-minute walk test in 1,212 patients before randomization to CABG (n=610) or me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 26 publications
0
14
0
7
Order By: Relevance
“…Среди больных с результатами ТШХ <300 м, напротив, смертность в течение 60 сут. после операции была выше, чем при медикаментозной терапии -ОР 3,24; 95% ДИ 1,64-6,83 (p<0,002), а при дальнейшем наблюдении достоверных различий между разными видами лечения не было -ОР 0,95; 95% ДИ 0,75-1,19 (p=0,626) [5]. Параметры этого анализа вполне способны объяснить парадоксальные, на первые взгляд, результаты исследования STICH, в котором не удалось продемонстрировать преимущества оперативного лечения больных ИБС со сниженной ФВ ЛЖ по сравнению с медикаментозной терапией, несмотря на имеющиеся международные рекомендации по этому поводу [3].…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Среди больных с результатами ТШХ <300 м, напротив, смертность в течение 60 сут. после операции была выше, чем при медикаментозной терапии -ОР 3,24; 95% ДИ 1,64-6,83 (p<0,002), а при дальнейшем наблюдении достоверных различий между разными видами лечения не было -ОР 0,95; 95% ДИ 0,75-1,19 (p=0,626) [5]. Параметры этого анализа вполне способны объяснить парадоксальные, на первые взгляд, результаты исследования STICH, в котором не удалось продемонстрировать преимущества оперативного лечения больных ИБС со сниженной ФВ ЛЖ по сравнению с медикаментозной терапией, несмотря на имеющиеся международные рекомендации по этому поводу [3].…”
Section: Discussionunclassified
“…При вмешатель ствах на сердце ситуация несколько иная, оценка функционального статуса не входит в шкалы риска оперативного вмешательства [3,4]. В то же время есть сведения о возможном негативном влиянии низкого физического статуса на результаты операции у отдельных категорий больных [5,6]. В исследовании STICH (Surgical Treatment for Ischemic Heart Failure) у больных ишемической болезнью сердца (ИБС) с низкой фракцией выброса (ФВ) левого желудочка (ЛЖ) сниженная физическая работоспособность повышала риск ранней смертности после операции коронарного шунтирования (КШ) по сравнению с медикаментозной терапией, а у больных с высокой работоспособностью отмечена обратная зависимость -операция КШ улучшала прогноз [5].…”
Section: Introductionunclassified
See 1 more Smart Citation
“…[ 25 ] The ischemic LV dysfunction and poor exercise capacity are risk factors of increased mortality rates 5 years after CABG. [ 26 ] Exercise training improves exercise capacity associated with restoration of peripheral oxygen utilization after CABG. [ 27 ] Cardiac rehabilitation initiated in a home environment may more likely sustain physical and psychosocial changes than institution based programs over 1 year after CABG.…”
Section: Physical Healthmentioning
confidence: 99%
“…Moreover, as-treated and adjusted analyses to consider patient crossovers suggested an overall favorable effect of CABG on primary and secondary outcomes [ 57 , 58 ]. Final data derived from this trial suggest that the observed survival benefits of CABG in patients with severe LV dysfunction are related primarily to factors such as functional status assessed by a 6 min walk and/or the Kansas City Cardiomyopathy Questionnaire [ 59 ] and the interaction of angiographic severity of CAD, severity of LV systolic dysfunction, and severity of LV remodeling [ 60 ]. Patients with preserved effort tolerance but with multivessel CAD, lower EF, and higher end-systolic volume index were most likely to benefit from CABG, particularly with respect to long-term survival.…”
Section: Surgical Alternatives In the Therapy Of Severe Left Ventrmentioning
confidence: 99%